Notes on competencies in engineering education - Cargnin-Stieler, Marinez; Teixeira, Marcelo C. M. [UNESP]; Assunc¸ão, Edvaldo [UNESP] (My University, 2014)
The subject covered in this text is an excerpt of a larger project and presents discussions on teacher's competencies, in engineering education, and also technical and scientific competencies. There is a growing demand for engineering teachers and this raises concern with regards to the formation of these professionals in Brazil. This paper begins with the information collected by electronic mail sent to professors of all Electrical Engineering postgraduate programs in Brazil. The questions/suggestions requested included the advice that could be given to postgraduate students about to enter the teaching profession. This research, grounded in the studies of Braslavsk, Perrenoud, Masetto and Zabalza, among other studies, indicated a convergence towards three engineering professor competencies: in-depth knowledge about the subject to be taught (technical and scientific), knowing the teaching content and to know how to teach this content (pedagogicaldidactic competence). In light of these questions, a didactic and pedagogical approach course is proposed, to be addressed collaboratively in the engineering postgraduate program. One suggestion regards addressing case studies or problems experienced by teachers, where the teacher chooses problems or cases grounded in theories, and students assigned to solve them in the best possible way. This could represent an initial setting to discuss and consider the engineering teacher role. In engineering education and pedagogic formation there is a gap that needs to be closed, especially during the doctoral or master program, as this is when the engineering teacher or teaching candidate qualifies technically and scientifically to engage in researching and teaching.
Keywords: Early-career professionals; Engineering education; Engineering learning; Engineering teaching